Effect of flaxseed’s supplement on AMPKα2′s expression in non-diabetic and diabetic patients having follicular thyroid carcinoma on mitochondrial’s ATP synthase for TPC-1 cell line - Amena Alsakran; Afaf Aldahish; Amani Alotaibi; Dalal Alshaya; Elham Alzahrani; Mohammad Alshugeer; Manal Alduwish; Dalia Domiaty; Fatimah Albani; Wedad Al-Qahtani (Electronic Journal of Biotechnology, 2025)
Background: This study examined the effects of flaxseed oil supplementation on the expression of adenosine monophosphate-activated protein kinase alpha2 (AMPKα2) in male patients with follicular thyroid cancer. The objective was to assess whether flaxseed oil could enhance AMPKα2 activity, improve histological features, and reduce tumor cell viability, offering a potential therapeutic benefit for diabetic and non-diabetic patients. Results: A total of 303 patients, including 149 non-diabetic and 154 diabetic participants, received 1250 mg of flaxseed oil daily for one month. Flaxseed oil supplementation significantly improved tumor histology, with treated tissues showing organized follicular patterns and reduced fibrovascular cells compared to untreated tissues. Cell viability assays demonstrated a dose-dependent reduction in papillary thyroid carcinoma cell viability, with the strongest effects observed at flaxseed extract concentrations of 80, 50, and 30 µg/mL. Molecular analyses revealed increased AMPKα2 expression in both treated thyroid cancer tissues and cell line models, indicating enhanced protein activation. These findings suggest that flaxseed oil supplementation may inhibit tumor proliferation and improve histological organization in follicular thyroid cancer. Conclusions: Flaxseed oil supplementation activates AMPKα2, reduces tumor cell viability, and improves histopathological features in follicular thyroid cancer tissues. These results highlight the potential of flaxseed oil as an adjunctive therapy to enhance cancer management strategies, particularly in diabetic and non-diabetic patients with follicular thyroid cancer.How to cite: Alsakran A, Aldahish A, Alotaibi A, et al. Effect of flaxseed’s supplement on AMPKα2’s expression in non-diabetic and diabetic patients having follicular thyroid carcinoma on mitochondrial’s ATP synthase for TPC-1 cell line. Electron J Biotechnol 2025;76. https://doi.org/10.1016/j.ejbt.2025.03.006.